In silico analysis of Pax6 protein glycosylation in vertebrates. (December 2018) - Uslupehlivan, Muhammet; Şener, Ecem; Deveci, Remziye
Graphical abstract: Highlights: Bioinformatic analysis showed that Pax6 is a glycoprotein that have N- and mucin-type O-glycosylation modifications besides O-GlcNAcylation. Possible ying-yang positions were also identified that may play a role in the activation/inactivation of Pax6. 3D glycoprotein structure of Pax6 protein was generated for the first time. Our results may contribute to the understanding of how glycosylation affects the interactions of Pax6 protein and its binding partners. Abstract: Pax6 is a transcription factor that involves in the formation of the eye, brain, and central nervous system in vertebrates. Due to various roles in the eye morphogenesis, Pax6 interacts with DNA and various transcription factors via post-translational modifications. Post-translational modifications of Pax6 have been studied extensively but there is a paucity of information about the glycosylation. Here, we focused on predicting the glycosylation positions of Pax6 protein in vertebrates. Also, 3D protein and glycoprotein models were generated using I-TASSER and GLYCAM servers in order to understand the effect of glycosylation on the Pax6 protein structure. We predicted N-glycosylation, mucin-type O-glycosylation, O-α-GlcNAcylation, and O-β-GlcNAcylation positions on Pax6 protein besides O-GlcNAc modification. Moreover, we found ying-yang positions suggesting the presence of O-GlcNAcylation/phosphorylation competition in Pax6. As to 3D glycoprotein models of Pax6, Ser24, Ser65, and Ser74 residues at the PD domain of Pax6 protein was evaluated as a strong candidate for the DNA binding site. We suggest that determination of the glycosylation positions on 3D glycoprotein model will facilitate the understanding of glycosylation role on Pax6 protein interactions in transcription and intracellular activities.